A superelastic viscous damper for enhanced seismic performance of steel moment frames. (15th December 2015) - Silwal, Baikuntha; Michael, Robert J.; Ozbulut, Osman E.
Highlights: A hybrid passive seismic control device is proposed. The device combines shape memory alloy cables with a high damped butyl rubber. Nonlinear analyses are conducted to explore the effectiveness of the hybrid device. The proposed device can effectively enhance seismic performance of structures. Abstract: This study proposes a hybrid passive control device and investigates its performance in improving response of steel frame structures subjected to multi-level seismic hazards. The proposed superelastic viscous damper (SVD) relies on shape memory alloy (SMA) cables for re-centering capability and employs a viscoelastic (VE) damper that consists of two layers of a high damped (HD) blended butyl elastomer compound to augment its energy dissipation capacity. First, experimental tests are conducted to characterize behavior of SMA cables and VE damper and to assess the influence of various parameters such as displacement amplitude and loading frequency on their mechanical response. Then, an analytical model of a six-story steel special moment frame building with the installed SVDs is developed to determine the dynamic response of the structure. Nonlinear response history analyses are conducted to evaluate the behavior of controlled and uncontrolled buildings under 44 ground motion records. Results shows that SVDs can effectively mitigate dynamic response of steel frame structures at different seismic hazard levels and enhance their post-earthquake functionality.